2014
DOI: 10.1117/1.jmi.1.3.031006
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Roe and Metz receiver operating characteristic model: analytic link between simulated decision scores and empirical AUC variances and covariances

Abstract: Abstract. Modeling and simulation are often used to understand and investigate random quantities and estimators. In 1997, Roe and Metz introduced a simulation model to validate analysis methods for the popular endpoint in reader studies to evaluate medical imaging devices, the reader-averaged area under the receiver operating characteristic (ROC) curve. Here, we generalize the notation of the model to allow more flexibility in recognition that variances of ROC ratings depend on modality and truth state. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Roe and Metz (RM) proposed a model for the simulation of MRMC data that emulate confidence‐of‐disease data collected from such studies. Studies that have used this model for evaluating various MRMC analysis and sample size methods include those given in the Reference List . To account for the MRMC study design, the RM model generates continuous decision variable (DV) data according to a binormal model for which the nondiseased and diseased DV variances are equal for each test‐reader combination, while allowing the differences between the diseased and nondiseased DV means to vary across test‐reader combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Roe and Metz (RM) proposed a model for the simulation of MRMC data that emulate confidence‐of‐disease data collected from such studies. Studies that have used this model for evaluating various MRMC analysis and sample size methods include those given in the Reference List . To account for the MRMC study design, the RM model generates continuous decision variable (DV) data according to a binormal model for which the nondiseased and diseased DV variances are equal for each test‐reader combination, while allowing the differences between the diseased and nondiseased DV means to vary across test‐reader combinations.…”
Section: Introductionmentioning
confidence: 99%
“…A mixed effects ANOVA model (modalities and readers as fixed effects, cases as a random effect) was used to evaluate the significance of AUC for CE-bCT. As a check, we also conducted an analysis of each reader separately using a non-parametric ROC model implemented in the iMRMC software 19 .…”
Section: Methodsmentioning
confidence: 99%
“…OSEL scientists share their models and data with the public to facilitate the use and broader adoption of these computational tools and approaches. For example, anatomical models of the head (the MIDA model) and whole body models (the Virtual Family) can be downloaded from the IT'IS Foundation's website 12 , 13 The experimental and computational data from an FDA-led multi-laboratory study for fluid dynamics on generic medical devices can be found here; 14 the simulation and statistical tools for the VICTRE project are here 15 and here ( 65 , 66 ); the HIFU simulator here 16 Other software applications are being shared through Github 17 , such as the design of a generic inferior vena cava filter 18 and a risk assessment tool for assessing color additives 19…”
Section: Computational Modeling Researchmentioning
confidence: 99%